Sustaining a nursing best practice guideline in an acute care setting over 10 years: A mixed methods case study - Nadalin Penno, Letitia; Graham, Ian D.; Backman, Chantal; Fuentes-Plough, Jessica; Davies, Barbara; Squires, Janet (Frontiers in Health Services, 2022)
Background To improve patient outcomes many healthcare organizations have undertaken a number of steps to enhance the quality of care, including the use of evidence-based practices (EBPs) such as clinical practice guidelines. However, there is little empirical understanding of the longer-term use of guideline-based practices and how to ensure their ongoing use. The aim of this study was to identify the determinants and knowledge translation interventions (KTIs) influencing ongoing use of selected recommendations of an institutional pain policy and protocol over time from an organizational perspective and 10 years post implementation on two units within an acute care setting. Methods We conducted a mixed methods case study guided by the Dynamic Sustainability Framework of an EBP 10 years post implementation. We examined protocol sustainability at the nursing department and unit levels of a multi-site tertiary center in Canada. Data sources included document review (n = 29), chart audits (n = 200), and semi-structured interviews with nurses at the department (n = 3) and unit (n = 16) level. Results We identified 32 sustainability determinants and 29 KTIs influencing ongoing use of an EBP in acute care. Three determinants and eight KTIs had a continuous influence in all three time periods: implementation phase (0–2 yrs), sustained phase (>2–10 yrs.), and at the 10-year mark. Implementation of KTIs evolved with the level of application (e.g., department vs. unit) to fit the EBP within the context highlighting the need to focus on determinants influencing ongoing use. Sustainability was associated with continual efforts of monitoring and providing timely feedback regarding adherence to recommendations. KTIs used to embed recommendations into routine practices/processes positively influenced high adherence rates. Use of a participatory approach for implementation and sustainment and linking KTIs designed to incrementally address low adherence rates facilitated sustainment. Conclusion This research provides insight into the relationship between implementation and sustainability determinants and related KTIs during implementation and sustained use phases. Unique determinants identified by department and unit nurses reflect their different perspectives toward the innovation based on their respective roles and responsibilities. KTIs fostered changed behaviors and facilitated EBP sustainment in acute care. Findings confirm the concept of sustainability is a dynamic “ongoing process.”